Geochemical dispersion processes in deep cover and neotectonics in Coompana, Nullarbor Plain, South Australia. Issue 1 (1st December 2019) - González-Álvarez, Ignacio; Krapf, Carmen; Noble, Ryan; Fox, David; Reid, Nathan; Foss, Clive; Ibrahimi, Tania; Dutch, Rian; Jagodzinski, Liz; Cole, David; Lau, Ian; Pinchand, Tenten
Summary: Mineral exploration in regions under thick cover is challenging. This study looked into vertical geochemical dispersion processes through ~550 m of cover in the Coompana Province, South Australia. We collected new data from CDP008 drill hole (~680 m), which contains the most complete record of the cover sequence in this region including: (1) mafic volcanic basement; (2) ~140 m of undifferentiated fluvial sediments (Phanerozoic); (3) overlain by ~230 m of fluvio-lacustrine to marine Mesozoic deposits; and (4) followed by ~200 m of Cenozoic carbonates. Our study revealed that REE patterns in the basalts and the overlying sandstone package show similarities. Yet, no geochemical similarities existed with the Mesozoic units and the upper stratigraphic units. Regolith mapping of this area revealed intricate landscape patterns. These include numerous linear scarps, which trend NW-SE to N-S to NE-SW and experienced <10 m of displacement. When coupled with magnetic data, this scarp trend correlates with basement structural trends at depth and hence these scarps are interpreted as neotectonic features. Based on the geochemistry we concluded that: (1) the lower sandstone package contains a geochemical footprint of the basement rocks produced by vertical and lateral geochemical dispersion; (2) the Mesozoic sediments do not record vertical dispersion related to the underlying basement; (3) the top limestone units are a chemical barrier for vertical geochemical dispersion due to lack of permeability. They are an efficient stratigraphic boundary to produce redox gradients and therefore differential geochemical horizons; and (4) basement features identified from magnetic data are mimicked by linear surface landscape features. We pose that neotectonic surface features may record vertical geochemical dispersion from lower stratigraphic units. The relation between neotectonic structures and landscape geochemistry could have critical implications in mineral exploration under cover in Australia and in other similar landscape settings in the world.